Student’s Perception on the Effectiveness of Using Voki as a Learning Media to Improving Speaking Ability - Indriana Dewi Mawarni Marpaung; Sholihatul Hamidah Daulay (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
This study aims to explore and describe students’ perceptions of the use of the VOKI application in English speaking activities. The research employed a descriptive qualitative method to gain a comprehensive understanding of learners’ experiences. The participants consisted of 33 students from grade XII at SMKN 1 Bandar Masilam, North Sumatra. Data collection involved two instruments: a questionnaire using a five-point Likert scale and semi-structured interviews with 10 selected students for in-depth insights. These instruments were designed to measure various dimensions, including students’ opinions on the usefulness, ease of use, and impact of VOKI on their speaking skills. The collected data were analyzed using the stages of data reduction, data presentation, and conclusion drawing as suggested by Miles and Huberman. Findings revealed that students showed a generally positive perception toward the use of VOKI in their learning process. Most students highlighted four key benefits: the application’s effectiveness in improving pronunciation, its engaging nature, accessibility across devices, and its support for collaboration in speaking activities. Furthermore, the use of avatars and animated characters in VOKI made the learning process more enjoyable, reduced anxiety during speaking practice, and increased students’ confidence to speak English. These results suggest that integrating digital tools like VOKI can significantly enhance students’ motivation and participation in speaking activities, making it a valuable alternative to conventional classroom strategies. Overall, VOKI proved to be an interactive, accessible, and student-centered medium that supports the development of speaking proficiency in a creative and engaging manner.